Methotrexate Versus Methotrexate Plus Folic Acid in the Treatment of Moderate to Severe Plaque Psoriasis: A Randomized Clinical-Trial - Khadka, D.K.; Agrawal, S.; Dhali, T.K. (Nepal Journal of Dermatology, Venereology & Leprology, 2016)
Background: Psoriasis is a chronic, recurring inflammatory disease affecting the skin, joints and nails that has a significant negative impact on the quality of life. Efficacy of methotrexate versus combination of methotrexate plus folic acid in the treatment of psoriasis has been rarely assessed. Objectives: To compare the efficacy of methotrexate versus methotrexate plus folic acid in the treatment of moderate to severe chronic plaque psoriasis Material and Methods: Eighty patients with moderate to severe chronic plaque psoriasis were randomized to receive either methotrexate (group A) or methotrexate plus folic acid (group B). End point of treatment was 75% reduction in Psoriasis Area and Severity Index (PASI 75) score or upto 3 months, whichever was earlier. Patients were then followed up for a period of 12 weeks for assessment of relapse, DLQI and adverse effects. Results: Of 80 patients, 71 completed the treatment and follow up period (33 in group A, and 38 in group B). PASI 75 was achieved in 34/40(85%) patients in group A and 32/40(80%) patients in group B (P < 0.142). There was statistically significant number of patients who had greater adverse effect in methotrexate than in methotrexate plus folic acid (p=0.020). There was significant difference in the number of patients who relapsed during the follow-up period (P = 0.013) with more relapse in group B. Conclusion: Combination of methotrexate and folic acid developed lesser adverse effect and greater relapse in comparison to methotrexate alone. Nepal Journal of Dermatology, Venereology & Leprology, Vol.14(1) 2016, pp.29-36